2003
DOI: 10.1007/s00066-003-1097-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Hemoglobin Level Prior to Radiotherapy on Survival in Patients with Glioblastoma

Abstract: The results indicate that lower Hb level prior to radiotherapy for glioblastoma can adversely influence prognosis. This finding deserves further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…Nevertheless, several trials provide evidence of a correlation between low a hemoglobin level and local failure or survival rates in patients treated with radiotherapy. The association between low hemoglobin level, hypoxia, and local radiotherapy failure for head and neck [1,2,6,23,28,30] and other solid tumors has also been established [12,[25][26][27]. Unfortunately, to date the impact of hypoxia and low hemoglobin level has not been extensively studied in malignant gliomas as in the other solid tumors; thus, only limited data are available on the influence of this factor on clinical outcome of gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, several trials provide evidence of a correlation between low a hemoglobin level and local failure or survival rates in patients treated with radiotherapy. The association between low hemoglobin level, hypoxia, and local radiotherapy failure for head and neck [1,2,6,23,28,30] and other solid tumors has also been established [12,[25][26][27]. Unfortunately, to date the impact of hypoxia and low hemoglobin level has not been extensively studied in malignant gliomas as in the other solid tumors; thus, only limited data are available on the influence of this factor on clinical outcome of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few researchers have included Hb level in the analysis of prognostic factors and the results obtained are inconsistent [15,20,36]. Lutterbach et al [20] found that hemoglobin levels in GBM did not influence overall survival, while Odrazka et al [23] demonstrated that a low Hb level (≤ 12.0 g/dl) can adversely influence prognosis. Lutterbach et al [19] in a multivariate analysis of prognostic factors established that anemia may negatively influence outcome in patients with malignant gliomas.…”
Section: Background and Purposementioning
confidence: 99%
“…1,4,25,26 Anemia is also correlated with patient survival, quality of life and treatment compliance. It appears to be one of the most powerful prognostic factor after clinical stage and tumor size.…”
Section: Introductionmentioning
confidence: 99%
“…Operative resection forms the basis of treatment but it is not feasible to effectively resect beyond the limits of macroscopically visible tumor without drastically compromising neurologic function. Adjuvant radiotherapy, however, provides an improvement in the prognosis, increasing the median survival time to about 1 year [13,14,24,28,30,39]. The limited efficacy of radiation treatment is believed to arise from the poor response and apoptosis to ionizing radiation in the tumor cells [17].…”
Section: Introductionmentioning
confidence: 99%